The Impact of Dementia on Family Carers Using the ICF Framework - Grigoriou, Stavroulla; Pampoulou, Eliada; Kambanaros, Maria (My University, 2022)
Background and Objectives: The aim of the study was to explore the experiences of family carers of people with dementia (PWD) in Cyprus and to describe the impact of dementia on family carers using the International Classification of Functioning, Disability and Health (ICF) framework as a model to interpret the findings. Research Design and Methods: A questionnaire with multiple choice responses was developed based on previous work published by the Netherlands Institute for Health Services Research (NIVEL). Eighty-four family carers of PWD completed the questionnaire and sixteen others completed the pencil-paper version. The data were analyzed based on descriptive statistics. Results: The findings showed that family carers support PWD in several different life domains. The results from the questionnaire were mapped onto the ICF framework to determine the impact of dementia on carers’ lives. The results, according to the ICF, revealed that, on the whole, dementia carers experience negative changes to body function, activities and participation as a result of caring for PWD. Furthermore, family carers attribute the detrimental effects on their health and wellbeing to the impact of continuous care resulting from the dementia. Discussion and Implications: The findings provide valuable insight into the experiences of family carers of PWD in Cyprus, and the need for health professionals to support family carers. Taking into consideration the results of this study, dementia carers experience changes to their daily functioning because of the cared one’s health condition. This has been described as carer’s “third- party disability” in the literature.
Keywords: Family carers; Problems; ICF; Third-party disability; Impact